Grass-Like Structured Mesoporous Carbon as an Acid Red 119 Dye Adsorbent - Krisnandi, Yuni Krisyuningsih; Priantini, Tania; Faisal, Muhammad; Yunarti, Rika Tri; Saragi, Indah Revita; Gunlazuardi, Jarnuzi (Makara Journal of Science, 2019)
Grass-like structured mesoporous carbon was prepared by the soft-template method using triblock copolymer Pluronic F127, affording an organic–organic composite structure between phloroglucinol and formaldehyde. Thermogravimetric analysis revealed that the as-synthesized mesoporous carbon is stable to 900 °C, and X-Ray Diffraction (XRD) analysis confirmed the presence of carbon material structures at 2θ values of 22.020° and 42.420°. A hysteresis loop at relative partial pressures (P/Po) between 0.45 and 0.85 was observed in the N2 adsorption isotherm, indicating that the solid material exhibits mesoporous characteristics, with a homogeneous pore size distribution of 8.863 nm. Scanning Electron Microscope (SEM) images revealed that the bulk carbon surface exhibits a uniform grass-like structure. Furthermore, the as-synthesized mesoporous carbon was investigated for the adsorption of a diazo dye Acid Red 119, and it exhibited an adsorption capacity of 217.7389 mg/g; this capacity is 1.53 times greater than that of commercial activated carbon. Therefore, this mesoporous carbon is a potential adsorbent for the treatment of synthetic coloring waste.